Mild and Severe Obesity Reduce the Effectiveness of Lumbar Fusions: 1-Year Patient-Reported Outcomes in 8171 Patients. (18th November 2021) - Mulvaney, Graham; Rice, Olivia M; Rossi, Vincent; Peters, David; Smith, Mark; Patt, Joshua; Pfortmiller, Deborah; Asher, Anthony L; Kim, Paul; Bernard, Joe; McGirt, Matthew
Graphical Abstract: